Microsoft 70-342 : advanced solutions of Exchange Server 2013 - Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The new Exchange Server 2013 Advanced Solutions course provides full coverage of the knowledge and skills to design and develop business solutions using Exchange Server 2013. This new and exciting course will enable you to configure and deploy unified messaging in Exchange Server 2013 and provide the information needed to handle cross forest coexistence deployments, which are vital knowledge areas for the exam. This new Exchange 2013 course provides you the needed training to perform e-discovery and message records management. In addition, this course focuses on several important features of Exchange Server 2013 including implementing compliance solutions such as transport rules, message classifications and ethical firewalls. This Advanced Solutions course brings together all the features and basic skills learned in the Core Solutions (Exam 70-341) course using them to solve various business problems in Exchange Server 2013. "--Resource description page.
Title and publication information from resource description page (Safari, viewed March 23, 2017).
Keywords: Microsoft Exchange server -- Examinations -- Study guides; Client/server computing -- Examinations -- Study guides; Electronic books